Installed Hydropower Capacity and Carbon Emission Reduction Efficiency Based on the EBM Method in China - Liang, Dong; Tian, Ze; Ren, Fangrong; Pan, Jingjing (Frontiers in Energy Research, 2020)
This study employs 29 provincial-level administrative regions in China from 2013 to 2017 to evaluate the overall efficiency score of hydropower electricity generation in the three main regions of China. The EBM (Epsilon-based Measure) model with the DEA (Data Envelopment Analysis) method uses installed capacity data, labor force data, and equipment utilization hours as input indicators and electricity generation and CO2 emission reduction as output indicators. By comparing the efficiency values of the two indices of installed capacity and CO2 emission reduction, we are able to analyze the differences between installed hydropower electricity generation capacity efficiency and carbon emission reduction efficiency in various provinces and cities. The findings show that the western region is the best, followed by the central region and then the eastern region in terms of the input-output index level, total efficiency score of hydropower, and comparison of installed capacity-carbon emission reduction efficiency. Natural water resources and geographical advantages have a great positive effect on hydropower efficiency, while economic development has little effect on it. China should promote the sustainable development of hydropower according to local conditions and formulate and adopt countermeasures in line with the different circumstances between regions.